2021
DOI: 10.1145/3471928
|View full text |Cite
|
Sign up to set email alerts
|

Even if users do not read security directives, their behavior is not so catastrophic

Abstract: Turning believers into nonbelievers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…They found that younger participants between the ages of 18 and 25 were more susceptible to phishing than other age groups [31]. Lastly, Matyas et al investigated students' security behavior over the course of several years and found that secure behavior improved, despite less and less students reading the university's security directive [20].…”
Section: Students' Information Security Awarenessmentioning
confidence: 99%
“…They found that younger participants between the ages of 18 and 25 were more susceptible to phishing than other age groups [31]. Lastly, Matyas et al investigated students' security behavior over the course of several years and found that secure behavior improved, despite less and less students reading the university's security directive [20].…”
Section: Students' Information Security Awarenessmentioning
confidence: 99%
“…Education informatization has entered a new stage of development and is shifting from digital education to intelligent education supported by modern information technology such as big data analysis and artificial intelligence [1][2]. At present, large-scale online education has accumulated a huge amount of teaching behaviour data and knowledge resources [3].…”
Section: Introductionmentioning
confidence: 99%